2001
DOI: 10.1002/path.967
|View full text |Cite
|
Sign up to set email alerts
|

Caspase activation during spontaneous and radiation‐induced apoptosis in the murine intestine

Abstract: The aim of this study was to characterize the activation of caspase-3 along the crypt/villus axis in the normal and irradiated intestine and to compare active caspase-3 expression with existing apoptosis detection techniques. Small and large intestine were removed from mice at various time points after exposure to 8 Gy gamma-radiation. Positive apoptotic cells stained with an antibody against active caspase-3, haematoxylin and eosin (H&E) or TUNEL were scored in histological sections of small and large intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 15 publications
10
97
1
2
Order By: Relevance
“…As shown in Figure 2a, mice deficient in Brca2 had a significant increase in the number of histologically identified apoptotic bodies (P ¼ 0.004, n ¼ 6; all statistics were performed using a nonparametric Mann-Whitney test with a confidence level of 95%). We also scored apoptosis by counting the number of cells staining positively for the activated form of caspase 3 (Marshman et al, 2001). The same increase was observed (see Figure 2b; P ¼ 0.04, n ¼ 3), although the level of caspase 3 positivity was higher than that scored by the histological method.…”
mentioning
confidence: 77%
“…As shown in Figure 2a, mice deficient in Brca2 had a significant increase in the number of histologically identified apoptotic bodies (P ¼ 0.004, n ¼ 6; all statistics were performed using a nonparametric Mann-Whitney test with a confidence level of 95%). We also scored apoptosis by counting the number of cells staining positively for the activated form of caspase 3 (Marshman et al, 2001). The same increase was observed (see Figure 2b; P ¼ 0.04, n ¼ 3), although the level of caspase 3 positivity was higher than that scored by the histological method.…”
mentioning
confidence: 77%
“…Interestingly, these factors may be involved in apoptosis cascade and therefore affect the homeostasis of intestinal epithelia (Baserga et al 2004;Jones and Gores, 1997). The apoptosis rate of intestinal epithelia inversely correlates with villus height and crypt depth and is accelerated by oxidative stress (Marshman et al 2001). Many studies have shown that the expression of Hsp70 was induced to prevent apoptosis and necrosis by gastrointestinal lesion of stress (Oyake et al 2006;Wada et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Identification and quantification of apoptotic bodies were performed using two techniques including staining for activated caspase 3 (Cell Signaling Technology, Beverly, MA) and routine morphological assessment following hematoxylin and eosin staining of sections. Morphological changes included the presence of nuclear condensation, perinuclear clearing, and cell shrinkage (19,37). The apoptotic index was calculated as the numbers of apoptotic bodies per 100 crypt cells.…”
Section: Methodsmentioning
confidence: 99%